Giving Preparative Thin-Layer Chromatography Some Tender Loving Care - Hayward, John J.; Mader, Lavleen; Trant, John F. (Synthesis, 2022)
Preparative thin-layer chromatography (prepTLC) is a commonly used method of purification suitable for small-scale reactions. However, descriptions of the preferred methodology to load, run, and recover samples from prepTLC are non-standard and varied, making it part of the ‘hidden curriculum’ of laboratory techniques. In this article we report on the simple, cost-effective methods we use to load and collect samples from a plate, which enhance the convenience, speed, and precision of this technique.
Keywords: laboratory technique; chromatography; separation science; thin-layer chromatography; tools